A forecasting model for assessing the influence of the components of technological growth on economic security - Ilyash, Olha; Lupak, Ruslan; Kravchenko, Maryna; Trofymenko, Olena; Duliaba, Natalia; Dzhadan, Iryna (Business: Theory and Practice, 2022)
The system of indicators for assessing the impact of the components of technological growth on economic security is generalised. This task is carried out by selecting a system of indicators (40 indicators), which, on the one hand, are consistent with one another and with key indicators used in analysing the state of economic security, and which are identified by the components of technological development, on the other hand. The standardisation of the values of initial data i.e. indicators, the determination of the degree of their deviations from the reference parameters and further integral assessment helped to find a generalised indicator of the state of development and the influence of technological growth on the parameters of the system of economic security. The purpose of the study is to test tools for forecasting modelling of the results of assessing the impact of technological growth on economic security. In accordance with the purpose, the level of relationships between the indicators of technological growth and the level of economic security is assessed. High, average and low levels of their relationship is revealed. The obtained results made it possible to forecast the rates of technological growth, perform exponential smoothing of the forecast estimates of the impact of the components of technological growth on economic security and employ damping measurement of the forecast level of the dependence of technological growth and economic security. Taking into account trends in technological growth, the system of indicators of the forecasting model for assessing economic security is expanded. The accuracy of the forecast is determined by the limits of the analysed period of the dynamics of the indicators – from 2013 to 2019, considering the impact of changes in the methodology for calculating individual input data according to statistical sources for the period under study. The use of forecasting models to assess the impact of technological development on Ukraine’s economic security will help identify political, economic, social and technological factors that will stimulate investment, strengthen economic openness, increase the volume and share of domestic high-tech exports, and thus, strengthen economic security.